2021
DOI: 10.1080/0309877x.2021.1932773
|View full text |Cite
|
Sign up to set email alerts
|

‘Fair and square’: what do students think about the ethnicity degree awarding gap?

Abstract: In UK higher education, minority ethnic students are less likely to graduate with a good degree than their White British counterparts, even when prior attainment is considered. Until recently, concerns about this ethnicity degree awarding gap have not received the research attention it deserves. In this paper, we contribute to this gap in knowledge with a focus on how students make sense of the difference in degree outcomes by ethnicity. Informed by 69 in-depth interviews with minority and majority ethnic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Initial analysis revealed that there was an awarding gap for UKME students. This was consistent with the University sector as a whole (Sotiropolou, 2021;Wong et al, 2021). As Advance HE report in their detailed analysis:…”
Section: Student Award Datasupporting
confidence: 79%
“…Initial analysis revealed that there was an awarding gap for UKME students. This was consistent with the University sector as a whole (Sotiropolou, 2021;Wong et al, 2021). As Advance HE report in their detailed analysis:…”
Section: Student Award Datasupporting
confidence: 79%
“…Universities have to ensure that young undergraduate students have role models whom they can approach for advice 29,30 . All of which can be applied to marine sciences.…”
Section: Discussionmentioning
confidence: 99%
“…Minority ethnic students in UK higher education are proportionally better represented in STEM (26.9%) than in non-STEM (17.4%) degrees (AdvanceHE, 2020), with around 25% of all UK-domiciled university students being identified as from a minority ethnic background. Whilst there is growing awareness and research in UK higher education on structural racism and inequalities, there are also concerns and recognitions that the experiences, trajectories and outcomes of minority ethnic students in STEM education are more challenging and difficult than their White British counterparts (Wong, 2016b;Wong, ElMorally & Copsey-Blake, 2021a). This article offers a qualitative and longitudinal study into the STEM degree journeys (Year 1, Year 2, Year 3) of three minority ethnic women, with the aim to document and detail their identity development and trajectory over the course of their undergraduate degree.…”
Section: The Studymentioning
confidence: 99%